2020
DOI: 10.1038/s41390-020-0876-8
|View full text |Cite
|
Sign up to set email alerts
|

Later cooling within 6 h and temperatures outside 33–34 °C are not associated with dysfunctional autoregulation during hypothermia for neonatal encephalopathy

Abstract: Background: Cooling delays, temperature outside 33–34°C, and blood pressure below the mean arterial blood pressure with optimal cerebral autoregulation (MAP OPT ) might diminish neuroprotection from therapeutic hypothermia in neonates with hypoxic-ischemic encephalopathy (HIE). We hypothesized that longer time to reach temperature <34°C and having temperature outside 33–34°C would be associated with worse autoregulation and greater brain injury. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…After that, NIRS became standard clinical care for HIE in our NICU, and the IRB waived the requirement for written consent. Sixty-six neonates in this study were reported in at least one of our past reports ( 4 7 , 15 18 ). Four neonates contributed new data to the study.…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations
“…After that, NIRS became standard clinical care for HIE in our NICU, and the IRB waived the requirement for written consent. Sixty-six neonates in this study were reported in at least one of our past reports ( 4 7 , 15 18 ). Four neonates contributed new data to the study.…”
Section: Methodsmentioning
confidence: 91%
“…The associations between each neonate's autoregulation and brain injury parameters were additionally analyzed with adjustments for sex, PaCO 2 level, perinatal insult score, vasopressor use, and presence of electroencephalographic seizures. We selected these covariates because of their potential associations with autoregulation and brain injury (15,23,(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No ano de 2017 no Japão, foi publicado um estudo que utilizou dados do "Baby Cooling Registry of Japan", que utiliza hipotermia ativa; encontrou que o resfriamento foi iniciado 6 horas após o nascimento em 96,6% dos casos; após o início da hipotermia, a temperatura corporal alvo foi atingida em uma média de 94 minutos (DP 154), e o resfriamento foi obtido em média com 312 minutos de vida (DP 183), mostrando que mesmo com hipotermia passiva, os dados do nosso estudo conseguiram demonstrar um desempenho semelhante ao das tecnologias avançadas (35) .Um outro estudo recente, realizado nos Estados Unidos e publicado nesse ano, avaliou o tempo de resfriamento e as variações de temperatura. A média de tempo para atingir a temperatura alvo foi de 240 ± 96 minutos (36) .…”
Section: -Tempo Para Atingir Temperatura Alvounclassified